Integrated pest management farmer field school of Chinese cabbage for young farmers in Batu City (University of Merdeka Malang, 2024)
The Abinaya Milenial Youth Farmers Group in Sumber Brantas Village, Bumiaji District, Batu City, faces significant challenges in cultivating Chinese cabbage due to a high incidence of clubroot disease caused by Plasmodiophora brassicae, with infection rates reaching 50–80 percent, leading to crop failure. The overuse of synthetic pesticides has resulted in pathogen resistance. Therefore, we adopted an integrated pest management (IPM) approach focusing on long-term prevention by integrating ecologically-based control techniques. The principles of IPM include managing healthy plants, preserving natural enemies, monitoring, and enhancing farmers' ecological understanding to become IPM experts. Through the IPM Farmer Field School (IPM-FFS), we aimed to implement ecological IPM, improve agroecosystem health, and support sustainable agriculture through participatory extension methods. Activities were conducted from June to November 2023 in Sumber Brantas Village, Bumiaji District, Batu City. The activities included surveys, planning, socialization, teaching, training, and follow-up. The IPM-FFS successfully developed standard operating procedures for Chinese cabbage management, increasing farmers' knowledge of IPM by 85 percent. The adoption of IPM reduced the incidence of clubroot disease to 20 percent, increased production by 420 kg, and reduced production costs by IDR 403,000 on an area of 400 m2. Farmers independently produce compost, compost tea, botanical pesticides, mycorrhizae, and fungicides through the IPM-FFS, empowering them in sustainable agriculture.